The first discovery of severe fever with thrombocytopenia syndrome virus in Taiwan - Lin, Tsai-Lu; Ou, Shan-Chia; Maeda, Ken; Shimoda, Hiroshi; Chan, Jacky Peng-Wen; Tu, Wu-Chun; Hsu, Wei-Li; Chou, Chi-Chung (Emerging microbes & infections, 2020)
Severe fever with thrombocytopenia syndrome (SFTS), an emerging tick-borne zoonosis, has been rapidly spread in many Asian counties since 2010, which raises the great concern in East Asia. Nevertheless, the infection status of SFTS in Taiwan remains unclear. To investigate the existence of SFTSV in Taiwan, a total of 151 serum samples collected from 31 sheep, 63 bovine and 57 dogs were enrolled this study. Furthermore, 360 adult female Rhipicephalus microplus were also included. One-step RT-nested PCR and IgG ELISA were conducted to test SFTSV specific RNA and antibodies, respectively. The result provided the first evidence of the existence of SFTSV RNA and antibodies in ruminants and ticks in Taiwan.